Experiencing Hektor Character in the Iliad - Kozak, Lynn (Bloomsbury Academic, 2016)
This book presents a rigorous philological examination of every instance where Hektor enters the Iliad, analysing each entrance's narrative context and style. In so doing, the author challenges and destabilises previous popular and scholarly assumptions about Hektor, and about the Iliad as a whole.